Perencanaan Pusat Pelatihan dan Pengembangan UMKM dengan Konsep Arsitektur Ekologis di Kabupaten Banyumas - Sofiya, Jita; Yohanes Wahyu Dwi Yudono; C. Dwi Istiningsih (ReTII, 2024)
MSMEs play an important role in the Indonesian economy, contributing 60.34% to the national GDP and absorbing 97% of the workforce. Banyumas Regency, which has 8,561 MSMEs, ranks fifth in Central Java. However, the unemployment rate in Banyumas is still high, reaching 6.35% in 2023. The main causes of unemployment are limited job opportunities, lack of capital, and human resource skills that are not in line with market needs. This research aims to design an MSME Training and Development Center in Banyumas as a strategic solution in improving the skills of the workforce, expanding the marketing of MSME products, and reducing unemployment. A qualitative approach is used to describe the site conditions, while quantitative methods are used to calculate the number of users and space. The results of this research are expected to encourage sustainable local economic growth, optimize the potential of MSMEs, and create new jobs in Banyumas.